2000
DOI: 10.1046/j.1523-5378.2000.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating T‐Cell Response to Helicobacter pylori Infection in Chronic Gastritis

Abstract: The results suggest that a shift toward a balanced Th1-Th2 response due to an increase in antigen-induced IL-4 production from CD4+ T cells follows eradication. We suggest that the downregulation of mucosal inflammation consequent on reduction in antigen levels or removal of downregulation after eradication of H. pylori contributes to this shift in cytokine balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
(41 reference statements)
3
35
0
1
Order By: Relevance
“…Thus in the protective immune response to H pylori, Th1 and Th2 are needed. It must have a balance between Th1 and Th2 to achieve immune protection and to prevent tissue from damaging by serious inflammation [23] . In our study, before challenge by alive H pylori, the levels of IFN, IL-12, IL-4 and IL-10 were significantly higher in the groups with chitosan than in other groups without adjuvant, indicating that in the early stage of immune, they induce immune response to both Th1 and Th2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus in the protective immune response to H pylori, Th1 and Th2 are needed. It must have a balance between Th1 and Th2 to achieve immune protection and to prevent tissue from damaging by serious inflammation [23] . In our study, before challenge by alive H pylori, the levels of IFN, IL-12, IL-4 and IL-10 were significantly higher in the groups with chitosan than in other groups without adjuvant, indicating that in the early stage of immune, they induce immune response to both Th1 and Th2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that infection with this pathogen triggers a Th1-type immune response, i.e., effector CD4 ϩ T cells producing gamma interferon (IFN-␥) but not interleukin-4 (IL-4), IL-5, or IL-13 in response to infection (2,26,38,39). However, this response does not enable the immune system to clear the infection and may instead be detrimental to tissue integrity.…”
mentioning
confidence: 99%
“…A similar mucosal response in immune mice following oral challenge with C albicans, has shown protection to include a positive paracrine loop involving IL-4 and nitric oxide (11). The data in these studies show not only a low baseline IL-4 secretion, but also an absence of the 'switch' and of the antigen-induced enhancement of cytokine secretion, which characterize an effective response to eradication (8). It is not clear whether the defective 'switch' characteristics reflect the primary defect of low IL-4 secretion or persisting bacterial colonization.…”
Section: Commentmentioning
confidence: 73%
“…Most mucosal T cells in patients infected with H pylori, secrete cytokines characteristic of a Th1 response (7). Following successful eradication, the cytokine pattern switches to one more characteristic of a balance between Th1 and Th2 cells, the so-called Th0 response (8). Mucosal cultures from patients with gastric cancer or precancer showed an extreme Th2 polarization, with high levels of IL-4 and an absence of IFN-γ (9).…”
Section: Peut-on Prévoir L'issue Du Traitement Suppressif D'helicobacmentioning
confidence: 99%